The readiness of MMU lecturers towards the implementation of blended learning - Hawa Rahmat; Rohaidah Mashudi; Mohd Hairul Anuar Razak; Nor Huda Abd Hamid; Nurhazlini Rahmat (Penerbit Universiti Kebangsaan Malaysia, 2019)
Many higher institutions have started to adopt and implement information and communication technology (ICT) as a source of flexible teaching and learning either in the classroom or outside the classroom. Multimedia University is among the eight universties in Malaysia that are awarded as Premier Digital Tech University by the Ministry of High er Education (MOHE) and the Malaysia Digital Economy Corporation (MDEC). In line with its statuses, MMU has implemented Blended Learning in teaching and learning. Therefore, the study is meant to examine the readiness of MMU lecturers towards the implementation of Blended Learning and to explore the current practice of Blended Learning among lecturers.The findings confirmed on the lecturer's readiness on Blended Learning implementation. The findings also revealed a good practice of the lecturers in implementing the Blended learning approach in their classes. The findings provide input on the integration of Blended learning in the process of teaching and learning. In conclusion, MMU lecturers are ready and equipped with adequate knowledge in implementing Blended Learning in the classes. It is hoped that the findings act as a valuable resource to recognise the various problems and issues in MMU from using technology to enhance the quality of teaching and learning. The analysis shows that adequate levels of technological, pedagogical, and content knowledge are essential for the take-up of e-learning at MMU.